The Physiological and Molecular Mechanism of Abscisic Acid in Regulation of Fleshy Fruit Ripening - Bai, Qian; Huang, Yun; Shen, Yuanyue (Frontiers in Plant Science, 2021)
The ripening of fleshy fruits is coupled with the degradation of both chlorophyll and cell walls, as well as changes in the metabolism of phenylpropanoids, flavonoids, starch/sucrose, and carotenoids. These processes are controlled by phytohormones and other factors, including abscisic acid (ABA), ethylene, auxin, polyamines, sugar, and reactive oxygen species. The ripening of climacteric fruits is controlled by ethylene and non-climacteric fruit ripening is regulated mainly by ABA. Also, ABA and ethylene may interact in both types of fruit ripening. ABA concentrations in fleshy fruits are regulated in response to developmental and environmental cues and are controlled by the relative rates of ABA biosynthesis and catabolism, the former mainly via 9-cis-epoxycarotenoid dioxygenases (NCEDs) and β-glucosidases and the latter via ABA 8'-hydroxylases (CYP707As) and β-glycosyltransferases. In strawberry fruit ripening, ABA is perceived via at least two receptors, Pyrabactin resistance (PYR)/PYR-like (PYL) and putative abscisic acid receptor (ABAR), which are linked separately to the conserved signaling pathway ABA-FaPYR1-FaABIl-FaSnRK2 and the novel signaling pathway ABA-FaABAR-FaRIPK1-FaABI4. Downstream signaling components include important transcription factors, such as AREB (ABA responsive element binding protein)/ABF (ABRE binding factors ABA responsive factor), ethylene response factor (ERF), and V-myb Myeloblastosis viral oncogene homolog (MYB), as well as ripening-related genes. Finally, a comprehensive model of ABA linked to ethylene, sugar, polyamines, auxin and reactive oxygen species in the regulation of strawberry fruit ripening is proposed. Next, new integrated mechanisms, including two ABA signaling pathways, ABA and ethylene signaling pathways, and ABA/ethylene to other phytohormones are interesting and important research topics in ripening, especially in non-climacteric fruits.